Comparative Forms of Adjectives In Karonese Language: A Study on Padan si Mbaru - Surbakti, Arya Alfines; Ambarita, Esron; Sitinjak, Vivi Novalia (Jurnal Pendidikan Impola, 2024)
This research aims to find out how comparative forms are formed in the Karonese language. The author used qualitative methods in carrying out this research because in-depth understanding and analysis are needed to complete this research. This research applied Herring’s theory in the book The Complete English Grammar Rules (2016). The results of this research show that there are two comparative forms found in padan si mbaru or Karonese language Bible, first by using a combination of the affix ter-en and the second using the article reh and the suffix -na. In the Karonese language, the comparative forms are formed by adding the affix ter-en in the base adjective and also using the article reh and the suffix -na in the bas adjective. Based on the results of this research, the author found 33 forms of comparative adjectives, namely, 6 forms using a combination of the affix ter-en and 27 forms of adjectives using the article reh and suffix -na.